Allogeneic Solid Platelet-Rich Plasma for Persistent Epithelial Neurotrophic Defects: A Protocol and Pilot Study. Issue 4 (12th April 2023) - Romano, Vito; Bignotti, Stefano; Forbice, Eliana; Bianchetti, Andrea; Almici, Camillo; Semeraro, Francesco
Abstract : Purpose: Here, we present the procedure to obtain allogeneic solid platelet-rich plasma (PRP) and its use in a pilot study of patients with persistent neurotrophic epithelial defects. Methods: We included 4 eyes of 4 patients with persistent neurotrophic epithelial defects unresponsive to other therapies from a single institution. PRP and thrombin were produced by the Department of Transfusion Medicine from healthy blood donors. PRP was activated in its solid form in the operating room with addition of thrombin and calcium gluconate 10% and applied on the cornea with fibrin glue and soft contact lens. Corneal healing time, corneal esthesiometry, visual acuity, Oxford staining score, Ocular Surface Disease Index questionnaire, and Schirmer I test were recorded. Anterior segment optical coherence tomography and in vivo confocal microscopy were also evaluated over the 4-month follow-up period. Results: The persistent epithelial defect healed in all patients in the first 10 days. During the follow-up, there was an absence of recurrences. For all patients, there was a reduction in Ocular Surface Disease Index questionnaire score (case 1: −55 points, −73.3%; case 2: −26.3 points, −58.4%; case 3: −56 points, −69.1%; case 4: −20 points, −26.6%; mean reduction: 39.3 points, 56.85%) and Oxford staining score (case 1, 2, and 3: 3 points decrease; case 4: 2 points decrease; mean reduction: −2.75 points). Conclusions: Allogeneic solid PRP in combination with fibrin glue may facilitate wound healing in neurotrophic persistent epithelial defects. Further prospective studies are needed to quantify its efficacy.